Comprehensive Analysis of the Expression and Prognosis for the DREAM Complex in Human Cancers - Wang, Lulu; Liu, Xiaowei (Frontiers in Genetics, 2022)
The DREAM complex is an evolutionarily conserved cell cycle regulating multi-protein complex. In addition to playing an essential function in the cell cycle, it also plays a vital role in various survival activities. Accumulating evidence suggests that the DREAM complex plays a crucial role in oncogenesis. However, the regulatory mechanism of the DREAM complex in cancer remains unclear. This study used multi-omics data from Cancer Genome Atlas and Cancer Cell Line Encyclopedia to comprehensively identify the DREAM complex in tumor samples from 33 cancer types. In the genomic landscape, we identified the missense mutation as the dominant alteration events. Expression analysis showed that the expression of methylation-mediated the DREAM complex was downregulated. In addition, we found that the expression of the DREAM complex can be performed to predict the survival of various cancer patients. Pathway activation analysis showed that the DREAM complex is related to apoptosis inhibition, cell cycle, DNA damage response, RAS/MAPK, and RTK signaling pathway activation. Importantly, through a comprehensive analysis of drug sensitivity genomics in cancer databases, we identified a number of potential drugs that may target the DREAM complex. In summary, this study revealed the genomic changes and clinical features of the DREAM complex in 33 cancers, which may also provide new insights for cancer treatment and may offer alternative options for the treatment of clinically refractory cancers.